Natural products as therapeutics for malignant melanoma: preclinical evidence and mechanism - Gao, Hongjin; Huang, Jianli; Zhang, Dengfeng; Li, Sixuan; Long, Shengzhi; Qin, Yuesi (Frontiers in Pharmacology, 2025)
Melanoma is one of the most common malignancies among fair-skinned populations. Natural products, a diverse group of bioactive compounds derived from plants and animals, have demonstrated inhibitory effects on melanoma growth, invasion, and metastasis. This review summarizes the mechanisms through which natural products inhibit melanoma progression and metastasis. These compounds are categorized based on their mechanisms of action. Many natural products have been found to induce apoptosis in melanoma cells through various signaling pathways. For instance, rhodopsin and the triazolylpeptidyl penicillin derivative TAP7f suppress the Wnt/β-catenin signaling pathway, thereby reducing melanoma cell proliferation and migration. Resveratrol and vitamin E delta-tocotrienol (δ-TT) inhibit caspase-dependent mitochondrial and endoplasmic reticulum stress pathways, inducing apoptosis in melanoma cells. Shikonin and plumbagin exert their antitumor effects through the mitogen-activated protein kinase/extracellular signal-regulated kinase (MAPK/ERK) signaling pathway. In addition, natural products such as silymarin, capsaicin, and ursolic acid exhibit multi-targeted anticancer effects with high efficiency and low toxicity by modulating various signaling pathways. These findings highlight the ability of natural compounds to regulate multiple biological targets, offering new directions and potential clinical applications in melanoma therapy. Natural product–based drug development holds great promise for overcoming current limitations in cancer treatment.